The Youth Janger Festival for the Preservation of Banyuwangi’s Local Cultural Heritage: Festival Janger Remaja dalam Upaya Melestarikan Budaya Lokal Banyuwangi - Ahmad Sulthoni Sulthoni; Dimas Priagung Banar; Charis Fathul Hadi; Hervina Nurullita (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The Janger performing art of Banyuwangi is a traditional cultural expression that combines dance, music, dialogue, and comedic oral performance in the Javanese language. Since the early twentieth century, Janger has served as a marker of cultural identity, a medium for moral education, and a space for social solidarity within the local community. However, over the past two decades, Janger has faced significant challenges, including a crisis of regeneration, linguistic shifts resulting from the mixture of Javanese, Osing, and Indonesian, declining performance frequency, and the commodification of art that threatens its authenticity. These conditions reflect a broader phenomenon occurring across Indonesia, where many traditional arts are pressured by modernization and globalization. Despite the rapid growth of cultural tourism in Banyuwangi—marked by major events such as Gandrung Sewu and the Banyuwangi Ethno Carnival—Janger has not gained a proportional position in cultural branding strategies. In fact, Janger holds strong potential as an authentic and educational cultural attraction, and it has been recognized as an intangible cultural heritage. The Youth Janger Festival program is proposed as a community-based cultural preservation effort aimed at revitalizing Janger through youth engagement, reinforcement of the Javanese language, and the implementation of a participatory festival, ensuring that this traditional art remains sustainable, adaptive, and rooted in Banyuwangi’s local identity.